Notes on South Indian Forest Types - Begue, L. (Indian Forester, 1960)
Mr. L. BEGUE, French Inspector General of Forests, visited some forests of Hyderabad and Aurangabad in 1954 after the 4th World Forestry Congress. More recently he attended the tour organized by the Government of India for the delegates to the 5th Session of the Asian Pacific Forestry Conference (1960). He could extend his trip from Pondicherry to the South of India and specially the hilly region of Madura district. A description of the regions he has visited, with a study of ecological conditions are given in the journal "Bois et Forets des Tropiques" NÂ°71, May-June 1960. We are enabled to give below, through the courtesy of Dr. P. Legris, Director French Institute, Pondicherry, a rough translation of a part Of this article which contains some comments on Champion's classification.